Pessoas com deficiência no cenário rural: concepção dos Agentes Comunitários de Saúde - Daiane Zeni; Marta Cocco da Costa; Fabiana Aparecida Rockemback; Deborah Tainara Schenkel; Jaqueline Arboit; Fernanda Honnef (Universidade Federal de Santa Maria, 2020)
Objective: to describe the conceptions of Community Health Workers about disabled persons who live in rural contexts. Method: descriptive-exploratory research, with a qualitative approach, performed in four municipalities in the northwest region of Rio Grande do Sul, Brazil. It had the participation of thirteen Community Health Workers. Data collection took place between January and February 2018 through semi-structured interviews, analyzed by thematic modality. Results: the conceptions of these professionals are especially anchored in the words "difficulty", "attention", "care", "contempt" and "access". Moreover, they reveal the poor knowledge about disabled persons living in the rural setting, by ignoring the different types of disabilities or pointing out conditions that do not fit their conception. Conclusion: we should highlight the urgent need for instrumentalization of these health professionals on the theme, in order to provide health care based on integrality and equity.